PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS POWTOON PADA MATA PELAJARAN IPS - Clara Alverina; Zerri Rahman Hakim; M. Taufik (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aimed to develop audio-visual learning media based on powtoon in the social science subject at the fourth-grade of the elementary school economic diversity material in Indonesia and to know the appropriateness and student’s respond to the learning media. The researcher used research and development (R&D) as the research method which there were three stages within it. The test was conducted to 31 fourth grade students at SD Negeri Bhayangkari, Serang city 2018/2019 period. The result of a design expert’s test showed 96% for the average score with a very feasible category. The result of a material expert’s test showed 88% for the average score with a very feasible category. The result of a language expert’s test showed 80% for the average score with a very feasible category. The result of the questionnaire showed 88.5% for the average score with a very feasible category. Based on research findings, the developed audio-visual learning media based on powtoon for fourth-grade students in elementary school was very feasible. It can be used in the teaching-learning process at economic diversity material in Indonesia of Social Science subject.Keywords : developing learning media, audio-visual, social science subject